INFLUENCE OF SEASON ON BIRTH OF PIGLETS IN SEMI-ARID REGION OF TAMIL NADU - P. Thirunavukkarasu; R. Amutha; R. Sakthivadivu; C. Nithya (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The study was structured to find out the seasonal influences on birth of piglets in tropical condition with the objective of probability in the birth of male and female piglets from 80 farrowing records for the period from 2017 to 2021. Depending on the season, male piglets are in more demand since they have to anticipate the demand for meat during festivals and other annual events. The parameters studied from farrowing records are litter size at birth and at weaning (42nd day). From this study, highest probability of male piglets were born during south west monsoon season where as the female piglets were born during winter season however, the pooled sex of piglets were born highest in winter season. It could be useful to the farmers who are in need of piglets for either meat production or breeding purpose.